Study of cell irregularity effects on the compression of closed-cell foams - Shi, Xiaopeng (2019)
Closed-cell aluminum foam is widely used as energy absorbing material. The cell regularity profoundly affects the mechanical behavior of this material. To investigate the influence of irregularity on elastic and plastic behavior of closed-cell foams, the compression behavior of Voronoi foams was simulated using the finite element method. The results show that with the increasing randomness of the foam, the elastic modules decrease a little while the collapse-strength decrease considerably. A theoretical analysis is conducted with the simple springs model. The results match well with simulation which shows theoretical analysis is reasonable. The Voronoi models were also compressed under different loading velocities and with different relative densities in simulation. The results reveal that foams with low regularity are more suitable for application in protective structures.